2020
DOI: 10.1093/milmed/usaa025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Compliance With Treatment Recommendations on Clinical Outcomes in Chronic mTBI: A TEAM-TBI Study

Abstract: Introduction Treatment approaches for mild traumatic brain injury (mTBI) have evolved to focus on active and targeted therapies, but the effect of compliance with therapy has not been investigated. The purpose of this study was to examine the role of patient compliance with prescribed therapies on clinical outcomes following mTBI. Materials and Methods Participants were aged 18-60 years with chronic (ie, 6+ months) mTBI sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…59 Previously, researchers have presented preliminary evidence that targeting treatment plans to the individual's unique response to chronic mTBI-related impairments in service members can improve overall symptoms, neurocognition, balance, and vestibular/ocular function. 60,61 However, more research in this area is sorely needed, as military personnel, perhaps moreso than civilians, may not seek treatment immediately for an mTBI (eg, deployment, social expectations, job demands). 12 Although research on veterans is critical, initiating treatment for symptoms and impairments related to mTBI long after the acute/subacute recovery period may not be the most precise strategy to reduce symptom burden and long-term comorbidities related to this injury.…”
Section: E351mentioning
confidence: 99%
See 1 more Smart Citation
“…59 Previously, researchers have presented preliminary evidence that targeting treatment plans to the individual's unique response to chronic mTBI-related impairments in service members can improve overall symptoms, neurocognition, balance, and vestibular/ocular function. 60,61 However, more research in this area is sorely needed, as military personnel, perhaps moreso than civilians, may not seek treatment immediately for an mTBI (eg, deployment, social expectations, job demands). 12 Although research on veterans is critical, initiating treatment for symptoms and impairments related to mTBI long after the acute/subacute recovery period may not be the most precise strategy to reduce symptom burden and long-term comorbidities related to this injury.…”
Section: E351mentioning
confidence: 99%
“…For example, prior studies have revealed that inconsistencies in diagnostic coding, co-occurring condition management, and issues with coordinating care across providers and settings can negatively impact the treatment of chronic mTBI 59. Previously, researchers have presented preliminary evidence that targeting treatment plans to the individual's unique response to chronic mTBI-related impairments in service members can improve overall symptoms, neurocognition, balance, and vestibular/ocular function 60,61. However, more research in this area is sorely needed, as military personnel, perhaps moreso than civilians, may not seek treatment immediately for an mTBI (eg, deployment, social expectations, job demands) 12…”
Section: Introductionmentioning
confidence: 99%
“…In many cases the main consequence of patient non-adherence is the lack of progress in treatment goals but in other circumstances health can be negatively impacted, especially with regard to medication use ( 5 , 6 , 11 ). In a recent article, Galey et al ( 12 ) looked at patients with persisting vestibular symptoms post-concussion and divided them into three groups; high, moderate and low compliance to clinical recommendations. Those in the high compliance group were able to improve their clinical outcomes and reduce symptom severity in comparison to patients in the moderate and low groups ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article, Galey et al ( 12 ) looked at patients with persisting vestibular symptoms post-concussion and divided them into three groups; high, moderate and low compliance to clinical recommendations. Those in the high compliance group were able to improve their clinical outcomes and reduce symptom severity in comparison to patients in the moderate and low groups ( 12 ). Encouraging adherence to appropriate health behavior is a critical component of improving health outcomes and patients often need support to modify their behavior and to recognize how their behavior influences their own health.…”
Section: Introductionmentioning
confidence: 99%
“…Although initially developed as a screening tool for the purpose of distinguishing between concussed and healthy adolescents, [1][2][3][4][5][6][7] there has been growing interest from clinical and research teams to use this tool outside the scope of screening and with different populations 8 (eg, addition of VOMS to Military Acute Concussion Evaluation 2 [MACE2] 9 ). Such examples include use in subacute and persistent time frames, 8,[10][11][12][13][14][15] use with adults, 8,15,16 and also for tracking recovery. 8,[16][17][18] Given changes that may occur throughout recovery (eg, expected improvements in some or all symptoms between 2 and 4 weeks), 19 and known differences in the vestibular and oculomotor systems that occur with aging, 20,21 findings from research conducted in younger and athletic populations may not be generalizable to adults following mTBI, especially those with symptoms that persist beyond expected recovery timelines.…”
mentioning
confidence: 99%